The role of post-migration living difficulties on somatization among first-generation immigrants visited in a primary care service - Massimiliano Aragona; Daniela Pucci; Sara Carrer; Elena Catino; Adriana Tomaselli; Francesco Colosimo; Montserrat Lafuente; Marco Mazzetti; Bianca Maisano; Salvatore Geraci (Annali dell'Istituto Superiore di Sanità, 2011)
The role of post-migration living difficulties (PMLD) on somatization was studied in 101 first generation immigrants visited in primary care. Premigratory traumas and post-traumatic stress disorder (PTSD) were also assessed. About one third of patients somatized. Sociodemographic variables were similar in somatizers and non-somatizers. Premigratory traumas, PTSD and the likelihood to report at least one serious or very serious PMLD were higher in somatizers. Four kinds of PMLD were more frequent in somatizers: worries about unavailability of health assistance, working problems, discrimination and poor social help. Traumas and PTSD influenced the effect of PMLD on somatization. Findings suggest that in specific samples of primary care immigrants severe premigratory traumas increase the sensitivity to PMLD and in turn distress due to PMLD amplifies the tendency to somatize.